The triple alliance: how a plant-ant, living in an ant-plant, acquires the third partner, a scale insect - Hashim, Rosli; Maschwitz, U.; Moog, J.; Saw, L.G. (2005)
Mutualistic associations between ants and plants often involve a third partner, scale insects (Hemiptera, Coccoidea). In southeast Asia, plant-ants of the genus Cladomyrma live together with coccoids in hollowed twigs of a wide range of ant-plants (myrmecophytes). Established colonies never lack sap-sucking scale insects and the ants appear to be dependent on the honeydew excretions of their trophobionts. Acquisition of scale insects thus seems to be an important step in the successful establishment of a new colony on a host plant. Coccoids may either be transported by a foundress ant on her nuptial flight (vertical transmission via co-dispersal) or ant and coccoid disperse on their own and associate anew during colony initiation (horizontal transmission). Here we test the assumption that founding gynes of Cladomyrma do not transport scale insects during their dispersal flight, and we determine when and how trophobionts are acquired. The results obtained in this study show that although coccoids are not carried by foundresses, their numbers within founding chambers of Cladomyrma increased with the founding stage. In all Cladomyrma species, colony-founding is claustral and the entrance hole into the nest chamber is first plugged with pith debris and later grows over by wound callus. However, access of trophobionts into hollow twigs is facilitated either by additional small openings ('secondary slits') produced by the foundress ant after hollowing out a nest chamber or by the maintenance of an orifice at the entrance hole during the founding period. Immature pseudococcids experimentally placed onto twigs close to a Cladomyrma foundation readily entered these slits. Exclusion experiments suggest that foundresses of C. petalae are less successful in rearing their first offspring if entry of coccoids into founding chambers is prevented.